Factors influencing vulnerability to climate change-related health impacts in cities - a conceptual framework - Jurgilevich, Alexandra; Käyhkö, Janina; Räsänen, Aleksi; Pörsti, Saara; Lagström, Hanna; Käyhkö, Jukka; Juhola, Sirkku (Elsevier BV, 2023)
Climate change will have adverse impacts on human health, which are amplified in cities. For these impacts, there are direct, indirect, and deferred pathways. The first category is well-studied, while indirect and deferred impacts are not well-understood. Moreover, the factors moderating the impacts have received little attention, although understanding these factors is critical for adaptation. We developed a conceptual framework that shows the pathways of climate impacts on human health, focusing specifically on the factors of urban environment moderating the emergence and severity of these health impacts. Based on the framework and literature review, we illustrate the mechanisms of direct, indirect, and deferred health impact occurrence and the factors that exacerbate or alleviate the severity of these impacts, thus presenting valuable insights for anticipatory adaptation. We conclude that an integrated systemic approach to preventing health risks from climate change can provide co-benefits for adaptation and address multiple health risks. Such an approach should be mainstreamed horizontally to all sectors of urban planning and should account for the spatiotemporal aspects of policy and planning decisions and city complexity.
Keywords: Climate risk; Health risk; Urban; Public health; Urban health; Pathway; Climate policy; Adaptation; Urban systems